CSR, CED, and Financial Performance: The Moderating Role of Leverage in IDX Transportation Sector - Ratnawati, Yayuk (CV. Ulil Albab Corp, 2026)
This study investigates the effect of Corporate Social Responsibility (CSR) and Carbon Emission Disclosure (CED) on firm performance (FP), with the Debt-to-Equity Ratio (DER) as a moderating variable, using data from transportation companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A purposive sampling method was employed, resulting in a total of 28 companies with 140 observations over five years. The data were analyzed using the EViews 13 software to perform panel data regression. The results reveal that CSR has a negative and insignificant effect on firm performance, suggesting that social initiatives may not provide immediate financial returns. In contrast, CED shows a positive and significant effect, indicating that transparent environmental disclosure enhances stakeholder trust and corporate legitimacy, thereby improving firm performance. Furthermore, DER negatively moderates the effects of both CSR and CED on firm performance, implying that higher leverage weakens the benefits of sustainability initiatives. These findings align with Agency Theory and Legitimacy Theory, showing that while financial constraints limit firms’ engagement in sustainability activities, transparency reinforces legitimacy and long-term value creation. The study contributes to the sustainability and corporate governance literature by emphasizing the importance of aligning financial structure with environmental and social strategies to achieve sustainable firm performance.